2003
DOI: 10.1038/sj.npp.1300023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Divalproex Combined with Olanzapine or Risperidone in Patients with an Acute Exacerbation of Schizophrenia

Abstract: This double-blind, randomized, multicenter study investigated the use of divalproex with an antipsychotic agent in patients hospitalized for acute exacerbation of schizophrenia. Patients (n = 249) who met DSM-IV criteria for schizophrenia were randomly assigned to receive olanzapine monotherapy, risperidone monotherapy, divalproex plus olanzapine, or divalproex plus risperidone for 28 days. Divalproex was initiated at 15 mg/kg/day and titrated over 12 days to a maximum dosage of 30 mg/kg/day. Olanzapine and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(122 citation statements)
references
References 32 publications
4
114
2
2
Order By: Relevance
“…The long-used drug valproate has recently been shown to be active in the brain as an HDAC inhibitor 62 and has been shown to be beneficial in the treatment of SZP when coadministered with neuroleptic medications. 68,69 HDACs exist in many distinct isoforms showing tissue-specific expression patterns. Administration of elevated doses of valproate to SZP inhibits multiple HDAC isoforms, increasing with similar efficacy the acetylated histone content of many different brain regions.…”
Section: Dnmt1 Mrna Overexpression In Pfc Of Szp Is Restricted To a Smentioning
confidence: 99%
“…The long-used drug valproate has recently been shown to be active in the brain as an HDAC inhibitor 62 and has been shown to be beneficial in the treatment of SZP when coadministered with neuroleptic medications. 68,69 HDACs exist in many distinct isoforms showing tissue-specific expression patterns. Administration of elevated doses of valproate to SZP inhibits multiple HDAC isoforms, increasing with similar efficacy the acetylated histone content of many different brain regions.…”
Section: Dnmt1 Mrna Overexpression In Pfc Of Szp Is Restricted To a Smentioning
confidence: 99%
“…al. 59 analyzed a clinical trial to assess efficacy of the association between divalproex and treatment with risperidone or olanzapine in acute schizophrenia and found a protective effect on increased total cholesterol in groups that used combined therapy. However, on the contrary, Isojärvi et al 20 found high triglyceride levels and low HDL levels in women with epilepsy taking valproic acid, compared with controls.…”
Section: Etiologic Factorsmentioning
confidence: 99%
“…Our article discussing valproic acid (VPA) augmentation of atypical antipsychotics in schizophrenia (Casey et al, 2003) re-stated our position that pharmacological doses of VPA affect GABA, and subsequently dopamine (Wassef et al, 1999. Dr Winterer's letter (Winterer, 2003) disagreed.…”
Section: Sirmentioning
confidence: 99%